Plant remains from 14th century Child Burial from the so-called Temple of Ceres, Mustis (N. Tunisia) - (:unkn) unknown (My University, 2023)
The Roman municipium Mustis (N. Tunisia) was founded at the end of the 2nd century BC in the area later called Africa Proconsularis. It was located in a strategic position, on one of the main roads between Carthage and Theveste. During its long history, many monumental buildings of a sacred, secular or defensive nature were erected there. One of those is the so-called Temple of Ceres, excavated in 2022 as part of the Tunisian-Polish project (Reading) African Palimpsest. The dynamics of urban and rural communities of Numidian and Roman Mustis (AFRIPAL) led by Tomasz Waliszewski from the Polish Centre of Mediterranean Archaeology, University of Warsaw, and Jamel el-Hajji from the Institut National du Patrimoine (Tunis). A burial pit with the child’s remains was discovered there, located on the axis of the temple almost in a north-south orientation. The tomb was covered with three ceramic tiles (tegulae). Radiocarbon studies allowed to date a burial to 14th century AD (1306-1365 AD), which is astonishing because it rather fitted in with the trends taking place in North Africa from the 3rd century onwards, especially during the Vandal and Byzantine period, when single burials are found intra muros in houses, temples, churches, etc. as is the case, for example, at Bulla Regia or Hippo Regius. In order to fully understand the burial, archaeobotanical samples were taken from the bottom and the fill. Analysis of the macroremains revealed the presence of cultivated plants such as Triticum aestivum/durum, Hordeum vulgare, Olea europaea, Lens culinaris and segetal or ruderal weeds, like Lolium sp., Euphorbia peplus which were part of the natural plant communities. The remains bear traces of intensive burning and the fact that they were exceptionally abundant compared to macroremains from other contexts of the trench suggests that they may have been deposited there deliberately. The importance of the research at Mustis is underlined by the fact that it is the se
Keywords: African Research